A comparison and decomposition of reform-era labor force participation rates of China's ethnic minorities and Han majority - Margaret Maurer-Fazio; James W. Hughes; Dandan Zhang (Institute for the Study of Labor (IZA), 2009)
This paper examines differences in China's ethnic majority and minority patterns of labor force participation and decomposes these differences into treatment and endowment effects using the technique developed by Borooah and Iyer (2005). Population census data are used to estimate gender-separated urban labor force participation rates (lfpr) using logit regressions which control for educational attainment, marital status, pre-school and school-age children, household size, age, and measures of local economic conditions. We focus on six minority groups (Hui, Koreans, Manchu, Mongolians, Uygurs, and Zhuang) and the majority Han. We find sizable differences between the lfpr of urban women of particular ethnic groups and the majority Han. Men's lfpr are very high and exhibit little difference between Han and ethnic minorities. For almost all pair-wise comparisons between Han and minority women, we find that differences in coefficients account for more than 100% of the Han-ethnic difference in labor force participation. Differences in endowments often have substantial effects in reducing this positive Han margin in labor force participation. Roughly speaking, treatment of women's characteristics, whether in the market or socially, tend to increase the Han advantage in labor force participation. The levels of these characteristics on average tend to reduce this Han advantage.
urn:nbn:de:101:1-20090513467
Keywords: J1; J2; J7; O1; O5; P2; 330; China; ethnic minorities; labor force participation; economic reform; population censuses; Städtischer Arbeitsmarkt; Ethnische Gruppe; Erwerbstätigkeit; Frauenerwerbstätigkeit; Systemtransformation; China